A methotrexate labelled dual metal oxide nanocomposite for long-lasting anti-cancer theranostics - Joyce L.Y. Tang; Shehzahdi S. Moonshi; Yuao Wu; Gary Cowin; Karla X. Vazquez- Prada; Huong D.N. Tran; Andrew C. Bulmer; Hang Thu Ta (Materials Today Bio)
We explored the feasibility of a self-assembled chitosan nanocomposite incorporating cerium oxide/nanoceria and superparamagnetic iron oxide nanoparticles (Chit−IOCO NPs), conjugated with methotrexate (MTX) and Cy5 dye, as an integrated cancer theranostic nanosystem (Chit-IOCO-MTX-Cy5). In this system, nanoceria serves as an anti-cancer agent, while the superparamagnetic iron oxide nanoparticles function as a negative contrast agent for MR imaging. This dual metal oxide nanocomposite is conjugated with MTX which is a structural analogue of folate, serving both as a targeting mechanism for folate receptors on cancer cells and as a chemotherapeutic drug. Chit−IOCO-MTX-Cy5 exhibited exceptional negative contrast in T2 and T2∗-weighted MRI, achieving a high relaxivity of 409.5 mM⁻1 s⁻1 which is superior to clinically approved agents. The nanocomposite demonstrated both pro-oxidative and antioxidative properties, significantly increasing reactive oxygen species (ROS) production in U87MG cells (1.4-fold change), which triggered apoptosis in these cancer cells. Simultaneously, it exhibited ROS scavenging activity in non-malignant endothelial cells (0.8-fold change). Intravenous infusion of Chit-IOCO-MTX-Cy5 (5 mg/kg MTX) led to significant tumor growth inhibition, indicating a synergistic enhancement of anti-cancer effects when combining MTX and nanoceria, compared to free MTX or nanoceria without MTX conjugation. Importantly, after treatment cessation, tumours in the nanocomposite group did not re-grow, while those in the free MTX group rapidly did. In vivo MR and fluorescence imaging revealed improved uptake and retention of Chit−IOCO-MTX-Cy5 in tumours compared to nanoceria without MTX. Notably, biosafety and biochemical analyses in mice showed no significant differences between the Chit−IOCO-MTX-Cy5 treatment group and control groups.